Self Talk Techniques in Adolescents to Complete Stress During the Covid-19 Pandemic at Smk Tridharma Lab. Gorontalo City UNG School - Nur Uyuun I. Biahimo; Firmawati; Nur Siti Rahma; Rifki Maulana; Vegi Bumulo (Journal of Universal Community Empowerment Provision, 2021)
Stress is a sign that a person's thoughts are becoming irrational or negative. Moreover, the current development of the Corona Virus shows that the public must be more aware of everything. This virus has an impact on people's lives around the world, one of which affects the psychology of teenagers where policies are made to reduce the impact of this pandemic. Where the mental condition of teenagers is increasingly being tested and not a few of them experience stress. The next step is to apply self-talk techniques that are beneficial for the psychological development of teenagers, which prioritize their positive thoughts over negative ones. The type of research used in this paper is a qualitative research with a descriptive method that explains how to overcome the stress experienced by teenagers during the Corona Virus pandemic as it is today with the Self Talk technique. The purpose of this community service is so that teenagers can overcome stress with Self Talk techniques during the covid 19 pandemic at Tridharma Lab Vocational School. School UNG Gorontalo City. From the results achieved with this activity, the school is very supportive and gives thanks to the Muhammadiyah University of Gorontalo in conducting counseling education in the form of leaflets and banners. The conclusion of this community service is that counseling can increase adolescent knowledge in training on Self Talk techniques